HbA1C dan Profil Lipid sebagai Prediktor Komplikasi Penyakit Jantung pada Pasien Diabetes Mellitus - Rezekiyah, Sholeha; Mustopa, Rd.; Karwiti, Witi; Garini, Ardiya; Edyansyah, Erwin (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the relationship between HbA1C and lipid profiles consisting of total cholesterol, triglycerides, HDL-C, and LDL-C as predictors of heart disease complications in patients with type 2 diabetes. The method used is observational analytic with a cross-sectional design. The results showed that the average HbA1c level was 9.01%; the average Lipid Profile levels were total cholesterol: 240.98 mg/dL, triglycerides: 170.08 mg/dL, HDL-C: 43.86 mg/dL and LDL-C: 161.56 mg/dL. The results of the Spearman correlation test showed a relationship between HbA1C and lipid profiles (total cholesterol, triglycerides, HDL, and LDL) in patients with type 2 diabetes at H. Abdul Manap Regional Hospital, Jambi City. The conclusion of the study is that type 2 DM patients have poor glycemic control (average HbA1C levels of 9.01%, with dyslipidemia (total cholesterol, triglycerides, and LDL-C increased and low HDL-C), a relationship was found between HbA1C and lipid profiles. Keywords: Diabetes Mellitus, Hba1c, Lipid Profile, Heart Disease